The meetings of the delegation of the Republic of Armenia with the German ambassador in Constantinople: Germany’s anti-Armenian plans (June 1918) - Petrosyan, Gegham (History and Culture, 2023)
The article analyzes the meetings of the delegation of the Republic of Armenia with the German ambassador in Constantinople. In this regard, special attention is paid to the non-pro-Armenian programs of Germany adopted in June 1918. The article considers the fact that the German military-political leadership made it clear to Armenian diplomats that in the complex and contradictory situation created in the region, it cannot jeopardize its relations with its ally Turkey for the sake of Armenians. The Armenian delegation in Berlin states that the Ministry of Foreign Affairs of Germany prevented Armenian diplomats from distributing the color map of Armenia’s borders, memos and other pro-Armenian diplomatic materials among the deputies of the Reichstag, the ambassadors of various countries accredited in Berlin, as well as a number of state, political and public figures.